DISTRIBUSI ZAKAT DI LAZISNU DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT KEBUMEN - Niken Lestari; Karomatun Sari’ah (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2024)
The aim of this research was to examine: How Zakat is distributed at LAZISNU Kebumen in an effort to improve the welfare of the people of Kebumen. This research is field research with a qualitative approach. Data collection techniques are carried out by collecting literature data from several literatures related to the issues raised, which basically differ in interpretation in understanding each division, and then the author examines and analyzes the existing data. Data analysis techniques are carried out by data reduction, which means summarizing, selecting, and sorting out the main things, focusing on important things, and looking for themes and patterns. The results of this study show that the pattern of distribution of Zakat funds in LAZISNU Kebumen is consumption management and productive management of Zakat. The consumptive model of distributing ZIS funds is not only staples but consumptive goods that are not only eaten but also dead assets cannot increase. While the productive model is usually distributed for business development, capital, and entrepreneurial training. The distribution of zakat to improve the welfare of the Kebumen community can be seen when a recipient of zakat has improved his economic level and can turn into a muzaki, no longer a mustahik.